2020
DOI: 10.1021/acs.biochem.0c00724
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Solution Structure of Human Fe(II)-Bound Acireductone Dioxygenase and Interactions with the Regulatory Domain of Matrix Metalloproteinase I (MMP-I)

Abstract: The metalloenzyme acireductone dioxygenase (ARD) shows metal-dependent physical and enzymatic activities depending upon the metal bound in the active site. The Fe­(II)-bound enzyme catalyzes the penultimate step of the methionine salvage pathway, converting 1,2-dihydroxy-5-(methylthio)­pent-1-en-3-one (acireductone) into formate and the ketoacid precursor of methionine, 2-keto-4-thiomethyl-2-oxobutanoate, using O2 as the oxidant. If Ni­(II) is bound, an off-pathway shunt occurs, producing 3-methylthiopropionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The modification of Mn(salen) by forming a supramolecular complex with zinc porphyrinate (due to the H-bond) increases the stability of the catalyst and promotes an increase in the substrate selectivity of the reaction [38] (Figure 2): The methionine salvage pathway (MSP) plays an important role in the regulation of a number of metabolites in prokaryotes and eukaryotes. The MSP is a universal pathway for the conversion of sulfur-containing metabolites into methionine [39]. The two Ni(Fe)ARD enzymes are members of the cupin structural superfamily, which includes Fe-Acetylacetone dioxygenase (Dke1) and cysteine dioxygenase.…”
Section: Nanostructure Science and Supramolecular Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…The modification of Mn(salen) by forming a supramolecular complex with zinc porphyrinate (due to the H-bond) increases the stability of the catalyst and promotes an increase in the substrate selectivity of the reaction [38] (Figure 2): The methionine salvage pathway (MSP) plays an important role in the regulation of a number of metabolites in prokaryotes and eukaryotes. The MSP is a universal pathway for the conversion of sulfur-containing metabolites into methionine [39]. The two Ni(Fe)ARD enzymes are members of the cupin structural superfamily, which includes Fe-Acetylacetone dioxygenase (Dke1) and cysteine dioxygenase.…”
Section: Nanostructure Science and Supramolecular Chemistrymentioning
confidence: 99%
“…The reaction pathway catalyzed by NiARD does not produce methionine, but the reaction does produce CO, which is a neurotransmitter. CO has been identified as an antiapoptotic molecule in mammals (mouse and human ARD isozymes) (Scheme 2 [39]). A study of the influence of metal ions Fe or Ni, as well as Co and Mn, on the catalytic activity of the mammalian enzyme showed that Fe-ARD, which catalyzes the first pathway, exhibits 10 times higher activity compared to Ni-, Co-, and Mn-containing enzymes that catalyze side reaction pathways.…”
Section: Nanostructure Science and Supramolecular Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…CO has been identified as an anti-apoptotic molecule in mammals. Recently, it was found that a human enzyme regulated the activity of matrix metalloproteinase I (MMP-I), which is involved in tumor metastasis, by binding to the cytoplasmic transmembrane tail peptide MMP-I [19].…”
Section: Catalysis With Acireductone Dioxygenases Ni(fe)ardmentioning
confidence: 99%